STRUCTURE OF THE SHADOW ECONOMY - Baratovich, Shakarov Allayor (PT. Antis International Publisher, 2024)
The shadow economy is an economic activity outside of government control. The problem of the shadow economy is most relevant in our time, since the scale of its spread is growing throughout the world and soon it may cover the entire sector of the economies of the world. The existence of the shadow economy creates a negative impact on society.